E-Book Development on Disaster Mitigation Materials to Improve Students’ Readiness Behavior in Facing Disasters - Raudhatul Jannah; Indri Yani; Lufty Hari Susanto (Bioedukasi: Jurnal Pendidikan Biologi, 2024)
Indonesia is one of the countries that has a high risk of natural disasters because it is traversed by the Pacific Ring of Fire. Post-natural disasters cause great losses, especially the emergence of various infectious and contagious diseases. To reduce this risk, it is necessary to build disaster preparedness behavior through education with attractive teaching materials. This research aims to develop e-books of disaster mitigation materials to improve students' disaster preparedness behavior. The population and sample were 29 students of SMAN 10 Bogor City class XD. The type of research used is Research and Development (R&D) research with a research design developed by Branch which consists of five stages, namely needs analysis, design, development, implementation, and evaluation. Data collection used interview and questionnaire techniques. Field trials were conducted using a one-group pretest-posttest design. The results of this study indicate that the e-book teaching materials developed have a very valid category. Based on the percentage of assessment by media experts of 96.43% and material experts of 97.50%. Students' preparedness behavior has increased after using e-book teaching materials on disaster mitigation material, from moderate to high levels with a percentage increase of 15.09% and an average n-gain of 0.53 with a moderate or moderately effective category. The development of e-book teaching materials that have been compiled and validated is categorized as very practical and effective as teaching materials. In terms of teacher questionnaire response, it obtained a percentage value of 95.83%, and student questionnaire response obtained a percentage value of 86.72%.